Organizational ethnography: "Clicks" among employees on private companies - Safriadi Safriadi; Hardiyanti Munsi; Andi Batara Al Isra (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This paper is a description of daily activities in private companies related to the social relations in workplace between employee, management, as well as consumer. Dyadic social relationship is built based on the construction of agreement between individuals in that organization. The interaction which happened in the construction of agreement caused social relations that occur in certain period. The quality of social relations depends on how is the content of that agreement, which is certainly guided by values and norms that had been agreed. Therefore, agreement that established sustainably in dyadic social relationships caused a clique. This clique manifested in agreement, a similarity in thought and feeling in the activities either in the workplace or outside. Moreover, there are other parts in organization interactions such as an act of talk about the negative things of others, which make that people feel disturbed. The gossip could be in a negative labeling form which is given to an individual or group that caused a disharmony in social relations. The methods of collecting data are observation, in-depth interview, literature study and documents. The research results show that clique and gossip in a company workplace are closely related to the harmony and disharmony of workplace, also contribute in the performances of employee in particular and company in general.